Membangun Manajemen Kearifan Lokal (Studi pada Kearifan Lokal Orang Banjar) - Agustina, Titien (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2018)
The Banjar people are the majority population of the Province of South Kalimantan, having diverse local wisdom. The uniqueness is in language, proverbs in oral communication, handycrafts on Banjar clothing or houses, knick-knacks and selected colors on Banjar traditional clothes, culinary possessions, as well as economic activities, community social activities, all characterized by uniqueness and diversity that is rich in philosophy. This research was conducted based on a review of the literature review with a qualitative approach. The aim is to identify and analyze the results of the local wisdom of the Banjar people in managing the uniqueness of the customs of culture, language, and the results of civilization that emerge as thoughts, inventions, feelings and intentions contained in the results of interacting with the external environment that give birth to values different from other ethnic groups